I do! I don't!: Revisiting the provisions of adultery and concubinage as applied to LGBTQI - De Castro, Shez Ann S. (Animo Repository, 2014)
This research study exerts effort to define and to give the purpose and objective of concubinage and adultery under the crimes against chastity in the Revised Penal Code of the Philippines. The researchers used the equal protection clause and the reasonableness test under the 1987 Philippine Constitution, as well as, the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR) that were used as the foundation of the Yogyakarta Principle, which addresses the extensive range of human rights standards and their application to issues regarding sexual orientation and gender identity. This research study also determines the purpose of the provisions under concubinage and adultery, and that is to help preserve the sanctity of marriage. The Philippine government failed to address the crimes committed by the LGBTQI community. Therefore, the researchers have concluded to amend and ratify the provisions under the Revised Penal Code, especially, the provisions on adultery and concubinage, to include that in the event that a husband or wife committed sexual infidelity with the same sex, they shall be also held liable and shall be given the same penalties similar to the penalties given to heterosexual people.